2021
DOI: 10.1021/acscentsci.1c00568
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Bias in a Layered Metal–Organic Topological Spin Glass

Abstract: The discovery of conductive and magnetic two-dimensional (2D) materials is critical for the development of next generation spintronics devices. Coordination chemistry in particular represents a highly versatile, though underutilized, route toward the synthesis of such materials with designer lattices. Here, we report the synthesis of a conductive, layered 2D metal–organic kagome lattice, Mn 3 (C 6 S 6 ), using mild solution-phase chemistry. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…Therefore, 2-Ti with no detectable structural disorder and three SGL transitions is an intriguing quantum magnet. Similar magnetic behavior has also been observed recently in Mn 3 (C 6 S 6 ) with a kagome lattice, no obvious structural disorder, and a spin-glass transition . These compounds are distinct from the conventional canonical spin glass (CSG), since structural disorder is an important ingredient for conventional spin glass such as CuMn.…”
Section: Resultssupporting
confidence: 77%
“…Therefore, 2-Ti with no detectable structural disorder and three SGL transitions is an intriguing quantum magnet. Similar magnetic behavior has also been observed recently in Mn 3 (C 6 S 6 ) with a kagome lattice, no obvious structural disorder, and a spin-glass transition . These compounds are distinct from the conventional canonical spin glass (CSG), since structural disorder is an important ingredient for conventional spin glass such as CuMn.…”
Section: Resultssupporting
confidence: 77%
“…Perhaps most excitingly, it has recently been demonstrated that redox-active radical ligands can introduce into MOFs both high electronic conductivity (0.45 S cm –1 ) and strong magnetic interactions, , despite the long distances between metal centers. This suggests that MOMs could form the basis for practical new quantum technology. …”
Section: Introductionmentioning
confidence: 99%
“…Due to its interfacial origin, the magnitude of this loop shifts and the so-called exchange bias field ( H EB , defined as H EB = , in which H C1 and H C2 are the left and right coercive fields, respectively) is inversely proportional to the thickness of the FM layer [ 13 ]. In view of their peculiar properties, magnetic materials unveiling strong EB behavior have gained much interest owing to their widespread applications in sensors [ 14 ], spintronic devices [ 15 , 16 ], drug carriers [ 17 ], and magnetic read heads for magnetic information storage devices [ 18 ]. In addition, AFM/FM multilayer (ML) thin films with strong perpendicular magnetic anisotropy (PMA) have become a key factor in improving magnetic logic chips, spintronic devices, and random-access memory devices [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%